2018
DOI: 10.1016/j.joca.2018.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetrics of ultrasound pathologies in osteoarthritis: systematic literature review and meta-analysis

Abstract: CRD42016039954.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 73 publications
3
35
0
Order By: Relevance
“…On the other hand, and in contrast to MRI, it is a widely available and inexpensive imaging method ( 13 ). Additionally, US features such as joint space narrowing and synovitis have been found to better correlate with pain than structural damage ( 23 , 24 ), and US might be good tool to measure changes in clinical trials ( 13 , 14 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, and in contrast to MRI, it is a widely available and inexpensive imaging method ( 13 ). Additionally, US features such as joint space narrowing and synovitis have been found to better correlate with pain than structural damage ( 23 , 24 ), and US might be good tool to measure changes in clinical trials ( 13 , 14 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown US to be reliable and valid for the evaluation of cartilage pathology in OA, and especially for large joints such as the knee ( 26 29 ), and US has demonstrated strong criterion validity with cartilage histology ( 25 ). The knee's hyaline cartilage has a normal thickness of 2 mm, and superficial regions can easily be evaluated by US ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that synovitis, when present, were mostly scored toward the lower end of the semi-quantitative scale as these grading scores were adopted from the scoring system created originally for rheumatoid arthritis [23], which is quantitatively different in inflammatory severity from OA [28]. Recent papers questioned the use or relevance of semi-quantitative scores in OA as it can lead to unequal distribution of the scores [29] and floor effects causing less sensitivity to detect an improvement in interventional trials [30].…”
Section: Discussionmentioning
confidence: 99%
“…7 Acceptable reliability of ultrasound-specific lesions provides the foundation for diagnostic or epidemiological studies using ultrasound imaging, but only a few previous studies have investigated the reliability of hip ultrasound in OA and they have mostly investigated individual findings and only by interpreting the same images. 6 Therefore, studies that include the differences in acquisition of images between the two operators in the assessment of reliability on ultrasound findings in people with hip OA are needed.…”
mentioning
confidence: 99%